Overexpression of Mammaglobin-A in Primary Breast Tissue Tumor and High Concentration of mRNA Mammaglobin-A in Peripheral Blood as Risk Factors for Metastatic Breast Cancer - Suryawisesa, Ida Bagus Made; Manuaba, Ida Bagus Tjakra Wibawa (Asian Pacific Journal of Cancer Biology, 2024)
Objective: There is still limited evidence for the use of biomarkers in breast cancer. However, mammaglobin-A in tissue and blood has recently been found as a promising biomarker for detecting metastases. Therefore, this study will examine the overexpression of mammaglobin-A in primary breast tissue tumors and the elevated concentration of mammaglobin-A messenger RNA (mRNA0 in peripheral blood as potential risk factors for breast cancer metastasis. Methods: The study was conducted at Sanglah General Hospital in Bali, Indonesia, from July 2017 to March 2018. It employed a hybrid research design, combining both cross-sectional (n = 70) and case-control (metastasis = 20 and non-metastasis = 20) approaches. Peripheral blood samples were collected using specialized L6 tubes and were analyzed for the expression of mammaglobin-A mRNA using quantitative real-time PCR. The diagnosis of breast cancer was established through open biopsy, considered the gold standard. Biopsy specimens underwent histopathological examination and standard immunohistochemistry (IHC) analysis to assess ER, PR, HER2, and Ki67 markers. The evaluation of mammaglobin-A protein expression was conducted via IHC at the Anatomical Pathology Laboratory of Prima Medika Hospital. Result: The mean mammaglobin-A mRNA level in the metastatic group was 11.59±1.37, while in the non-metastatic group was 8.17±1.27-fold change relative to the housekeeping gene beta microglobulin. The mean mammaglobin-A mRNA levels in the two groups were significantly different (p<0.05). Overexpression of mammaglobin-A in cancer tissue was 7.36 times more likely for metastasis compared to non-metastatic (OR = 7.36; 95% CI = 1.34-40.55; p = 0.013). Additionally, mammaglobin-A mRNA concentration was found to be nine times higher for breast cancer metastasis compared to the non-metastatic group (OR = 9.00; 95% CI = 2.15-37.66; p = 0.002). Conclusion: The mean mammaglobin-A level in the metastatic group significantly differs from that in the non-metastatic group. Overexpression of mammaglobin-A and a high concentration of Mammaglobin-A mRNA are influential risk factors for metastatic breast cancer.